O16.6 Basic science aids syphilis vaccine development: bloodstream spreading by the syphilis spirochete treponema pallidum. (14th July 2019) - Lithgow, Karen; Church, Brigette; Moon, Jenny; Houston, Simon; Burke, John; Swayne, Leigh Anne; Foster, Leonard; Cameron, Caroline
Abstract : Background: Treponema pallidum ssp. pallidum ( Tp ) causes syphilis, a sexually transmitted infection characterized by multi-stage disease and diverse symptoms . Tp undergoes rapid vascular dissemination, penetrating tissue, placental, and blood-brain barriers to access secondary infection sites via a process that is incompletely understood. The protein Tp0751 is an adhesin on the host-facing surface of Tp that mediates adherence to endothelial cells (ECs) lining blood vessel walls. This study explores Tp movement across endothelial barriers to enhance our understanding of Tp dissemination and identify host interactions that could be targeted for vaccine development. Methods: The methods of affinity chromatography and proteomics were used to identify receptor proteins on host ECs that are bound by Tp0751. Antibody inhibition studies revealed specific receptor regions required for binding. Endothelial barrier traversal was investigated with immunofluorescence and barrier permeability assays. Phosphoproteomics identified endothelial intracellular signaling pathways initiated by Tp0751 by exploring gain/loss of phosphoryl groups on proteins. Results: Here we show Tp uses Tp0751 to bind the 67 kDa laminin receptor (LamR) on human EC surfaces. Importantly, the same region of LamR is also targeted by meningitis-causing bacteria including Neisseria meningitidis and Streptococcus pneuomoniae . Further molecular analyses reveal that Tp and Tp0751 disrupt the architecture of human cell-cell junctions in blood vessel walls without altering overall barrier integrity. Phosphoproteomics demonstrates that ECs exposed to Tp0751 exhibit differential phosphorylation on proteins known to promote endothelial barrier traversal by leukocytes and pathogens. Conclusion: These studies suggest a common tissue invasion strategy exists for neuroinvasive pathogens and identifies an interaction that can guide vaccine development for syphilis and other neuroinvasive diseases. Further, exploring Tp barrier traversal reveals that Tp uses similar mechanisms as immune cells and neurotropic pathogens to invade tissues and cause the detrimental sequelae associated with syphilis. These studies enhance our understanding of Tp infection and facilitate targeted syphilis vaccine development. Disclosure: No significant relationships.